The association between professional value and occupational burnout among nurses working in the emergency department - Akbarilakeh, Maryam; Goodarzi, Fatemeh; Oroei, Mahbobeh (Social Determinants of Health, 2019)
Background: Burnout is one of the most common illnesses due to stress among nurses. Nurses should be able to respond to ethical conflicts by using professional value. This study aimed to determine the relationship between professional value and occupational burnout of nurses working in the emergency department of educational hospitals at Shahid Beheshti University of Medical Sciences in Tehran. Methods: This cross-sectional study included 241 nurses from 6 educational hospitals during 2018 by using convenience sampling. The Maslach Burnout questionnaire and a professional nursing questionnaire were used for collecting data. The data were described by mean±SD, frequency (percentage) and analyzed by Pearson correlation coefficient and linear regression using SPSS Inc. Released 2009. PASW Statistics for Windows, Version 18.0. Results: Of all participants 132 (54.8%) were female. The mean±SD of occupational burnout score was 70.71±15.25. The mean±SD of score for emotional exhaustion was 27.78±11.57, depersonalization was 13.34±5.37, the personal accomplishments was 29.64±10.63, and the professional value was 88.25±22.0. There was a significant reverse relationship between professional value score and occupational burnout score (r=-0.19, P=0.01, 95% CI=-0.23_-0.03). The demographic data was no associated with the occupational burnout (all P>0.05). Conclusion: Overall, occupational burnout in emergency department in nurses was high. According to the attained data, the professional value is one of the factors which has been associated to the occupational stress and burnout.